Gestión del cumplimiento de los acuerdos derivados de los conflictos sociales: un modelo de análisis desde la gestión pública y las políticas públicas - Balbuena Palacios, Patricia (2017)
Since the 21st century, in Peru, there has been an increase in social conflicts, mainly socio-environmental, linked to the growth of the extractive industry due to the boom in commodities. fte foregoing demonstrates a paradox between economic growth and governability that, in some cases, has resulted in episodes of extreme violence. In this scenario, the Peruvian State has developed important reforms and various tools for the management of social conflictivity through dialogue. However, the constant failure to comply with the agreements derived from the dialogue has generated the questioning of the various mechanisms. fte purpose of this article is to propose a model of analysis to study compliance with the agreements derived from the dialogue and suggest manners to improve them. fte data were recorded through tools like the bibliographic review, documental and semi-structured interviews. fte research concludes that the political content is fundamental for consensus, but its viability will depend on the technical implementation of the agreements and the promises reached. To this aim, it is proposed to explain the difficulties in the compliance management of the agreements based on three levels of analysis: a) state capacities; b) internal management of the agreement; and, c) governmental coordination. Exploratory hypotheses are being outlined for future research.